CAR T Cells Targeting Membrane-Bound Hsp70 on Tumor Cells Mimic Hsp70-Primed NK Cells - Bashiri Dezfouli, Ali; Yazdi, Mina; Benmebarek, Mohamed-Reda; Schwab, Melissa; Michaelides, Stefanos; Miccichè, Arianna; Geerts, Dirk; Stangl, Stefan; Klapproth, Sarah; Wagner, Ernst; Kobold, Sebastian; Multhoff, Gabriele (Frontiers in Immunology, 2022)
Strategies to boost anti-tumor immunity are urgently needed to treat therapy-resistant late-stage cancers, including colorectal cancers (CRCs). Cytokine stimulation and genetic modifications with chimeric antigen receptors (CAR) represent promising strategies to more specifically redirect anti-tumor activities of effector cells like natural killer (NK) and T cells. However, these approaches are critically dependent on tumor-specific antigens while circumventing the suppressive power of the solid tumor microenvironment and avoiding off-tumor toxicities. Previously, we have shown that the stress-inducible heat shock protein 70 (Hsp70) is frequently and specifically expressed on the cell surface of many different, highly aggressive tumors but not normal tissues. We could take advantage of tumors expressing Hsp70 on their membrane (‘mHsp70’) to attract and engage NK cells after in vitro stimulation with the 14-mer Hsp70 peptide TKDNNLLGRFELSG (TKD) plus low dose interleukin (IL)-2. However, a potential limitation of activated primary NK cells after adoptive transfer is their comparably short life span. T cells are typically long-lived but do not recognize mHsp70 on tumor cells, even after stimulation with TKD/IL-2. To combine the advantages of mHsp70-specificity with longevity, we constructed a CAR having specificity for mHsp70 and retrovirally transduced it into primary T cells. Co-culture of anti-Hsp70 CAR-transduced T cells with mHsp70-positive tumor cells stimulates their functional responsiveness. Herein, we demonstrated that human CRCs with a high mHsp70 expression similarly attract TKD/IL-2 stimulated NK cells and anti-Hsp70 CAR T cells, triggering the release of their lytic effector protein granzyme B (GrB) and the pro-inflammatory cytokine interferon (IFN)-γ, after 4 and 24 hours, respectively. In sum, stimulated NK cells and anti-Hsp70 CAR T cells demonstrated comparable anti-tumor effects, albeit with somewhat differing kinetics. These findings, together with the fact that mHsp70 is expressed on a large variety of different cancer entities, highlight the potential of TKD/IL-2 pre-stimulated NK, as well as anti-Hsp70 CAR T cells to provide a promising direction in the field of targeted, cell-based immunotherapies which can address significant unmet clinical needs in a wide range of cancer settings.